Acidic Mammalian Chitinase and the Eye: Implications for Ocular Inflammatory Diseases - Bucolo, Claudio; Musumeci, Maria; Musumeci, Salvatore; Drago, Filippo (Frontiers in Pharmacology, 2011)
Chitinases have an important role in the defence of organisms against chitin containing parasites. An acidic mammalian chitinase (AMCase) has been detected in epithelial cells in lung tissue samples taken from patients with asthma as well as in conjunctival epithelium of patients with inflammatory ocular diseases. Particularly, elevated AMCase activity has been observed in ocular tissues of patients with vernal keratoconjunctivitis, seasonal allergic conjunctivitis, and in patients affected by dry eye syndrome. This enzyme is induced via a TH2-specific, IL-13-dependent pathway. AMCase may thus be a key mediator of IL-13-induced responses in TH2-driven inflammatory ocular diseases.